The Cunning of Recognition in the Four Axioms of Existence - Povinelli, Elizabeth A. (Itinerari, 2023)
This essay examines the politics of late liberal settler recognition from the perspective four axioms of existence and from within a case study of the disinheritance of two sets of clans. After reviewing the author’s intellectual position with the literature on recognition, the essay argues that scholarship on recognition needs to be reframed within four axioms of existence emerging in critical theory in the wake of geontopower and then moves to a short overview of how this reframing might provide new methods to the study of contemporary cultural politics. The four axioms of existence are the entanglement of existence; the unequal distribution of power to affect the local and transversal terrains of this entanglement; the multiplicity and collapse of the event as the sine qua non of political thought; and the provincial racial and colonial history that informed liberal western ontologies and epistemologies and the concept of the west as such. The clans are the author’s own Simonaz clan of Povinellis that emerged at least by the turn of the 17th century in the Alpine village of Carisolo and the clans of the Karrabing in the Top End of the Northern Territory of Australia.